Global Financial Stability Report, September 2005 : Market Developments and Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2005)
This September 2005 issue of the Global Financial Stability Report highlights that financial conditions have remained broadly positive over the past six months, but some market developments diverged from consensus expectations of market participants. Long-term interest rates, instead of rising, as expected by some investors, have moderated, leading to a further flattening of global yield curves. This reflected cyclical factors, as market participants seemed to expect more moderate global growth and inflation, and structural factors such as a secular portfolio shift toward long-term bonds by pension funds and life insurance companies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet